The women's house of detention: a queer history of a forgotten prison - Ryan, Hugh (Bold Type Books, 2022)
The pre-history of the Women's House of Detention (1796-1928) -- Psychiatrists, psychologists, and social workers-the prison's -- Eyes, ears, and record keepers -- Where the girls are: Greenwich Village & lesbian life -- Firing Rosie the Riveter -- The long tail of the drug war -- Flickers of pride -- Conformity & resistance -- The gay crowds -- Queer women get organized -- The city's search for the perfect victim -- Gay lib and Black power.